Analysis Of Irgift.Id Promotion Strategies By Utilizing Tiktok Social Media In Increasing Sales Volume - Firdha Amalia Nareswari; Yanda Bara Kusuma (International Journal of Economics Development Research (IJEDR), 2024)
This research uses Irgift.id which is one of the business fields in the floriculture sector. The purpose of this study is to determine and analyze promotional strategies using the use of TikTok social media in an effort to increase sales volume. The research method used is descriptive qualitative method using SWOT analysis techniques and data collection techniques through in-depth interviews, observation and documentation related to promotional strategies in identifying strengths, weaknesses, opportunities, and threats at Irgift.id. Informants in this study include the owner or owner, employees, and consumers. The results of this study obtained IFAS results which showed strengths with a score of 2.69 and weaknesses with a score of 0.42. While the EFAS results show opportunities with a score of 2.31 and threats with a score of 0.74. Based on the SWOT analysis diagram, Irgift.id is in quadrant I using the SO strategy, namely the company has opportunities and strengths so that it can take advantage of existing opportunities so that the strategy that can be applied is to support the growth of agrarian policies (growth oriented strategy) to increase sales volume